Detection for Salmonella typhimurium ATCC 14028 on Sausage, Nugget, Meatballs, Otak-Otak, Tempura and Cilok Products Using the Kit Rapid Test - Sophian, Alfi; Muindar, Muindar (Poltekkes Kemenkes Gorontalo, 2021)
Testing for Salmonella typhimurium ATCC 14028 using a rapid test kit was carried out in the microbiology and molecular biology testing laboratory of the Food and Drug Administration in Gorontalo. Research using a rapid test kit is a simple study that requires a relatively shorter time than using conventional techniques. The purpose of this study was to see the work of the rapid test kit in detecting Salmonella typhimurium ATCC 14028 spiked on several food processed products. The sample consisted of 12 replications with 6 types of food products including sausages, nuggets, meatballs, otak-otak, tempura and cilok. Positive controls were made from Salmonella typhimurium ATCC 14028 phase 2 cultures, while negative controls used sterilized samples of sausage, nuggets, meatballs, otak-otak, tempura and cilok samples. The concentration of positive control used was taken from turbid work culture and equalized according to Macfarland standard 1. The data analysis was performed qualitatively based on the change in the colour of the kit in the sample which was compared to positive and negative controls. Based on the results of the study, it was found that all samples were detected Salmonella typhimurium ATCC 14028. This study concludes that the rapid test kit can be used to detect Salmonella typhimurium ATCC 14028 in sausage products, nuggets, meatballs, otak-otak, tempura and cilok